A 10, 300-year-old permafrost core from the active rock glacier Lazaun, southern Ötztal Alps (South Tyrol, northern Italy). Issue 2 (March 2015) - Krainer, Karl; Bressan, David; Dietre, Benjamin; Haas, Jean Nicolas; Hajdas, Irka; Lang, Kathrin; Mair, Volkmar; Nickus, Ulrike; Reidl, Daniel; Thies, Hansjörg; Tonidandel, David
Abstract : Two cores were drilled on rock glacier Lazaun in the southern Ötztal Alps (N Italy). The average ice content of core Lazaun I is 43 vol.% and of core Lazaun II is 22 vol.%. Radiocarbon dating of plant macrofossil remains of core Lazaun I yielded ages ranging from 8960 cal yr BP at a depth of ca. 23.5 m to 2240 cal yr BP at a depth of 2.8 m, indicating that the ice near the base is approximately 10, 300 yr old. The rock glacier was intact since that time and the ice persisted even during warm periods of the Holocene. An ice-free debris layer between 16.8 and 14.7 m separates the rock glacier into two frozen bodies. Inclinometer measurements indicate that both frozen bodies are active and that deformation occurs within a shear horizon at a depth of 20–25 m at the base of the lower frozen body and to a minor extent at a depth of approximately 14 m at the base of the upper frozen body. The ice-free debris layer in the middle of the Lazaun rock glacier indicates a more than five centennial long drought period, which dates to about 4300–3740 cal yr BP.